2015
DOI: 10.1192/bjp.bp.114.157685
|View full text |Cite
|
Sign up to set email alerts
|

Different outcomes of never-treated and treated patients with schizophrenia: 14-year follow-up study in rural China

Abstract: Many patients with schizophrenia still do not receive antipsychotic medication in rural areas of China. The 14-year follow-up showed that outcomes for the untreated group were worse. Community-based mental healthcare, health insurance and family intervention are crucial for earlier diagnosis, treatment and rehabilitation in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 42 publications
8
100
1
3
Order By: Relevance
“…Interestingly, different results were found in a retrospective cohort study of individuals with schizophrenia whose access to antipsychotic treatment had been restricted. In this cohort from rural China, those who had access to antipsychotics did substantially better after 14 years than those without access.…”
Section: Efficacy Effectiveness and Tolerabilitymentioning
confidence: 99%
“…Interestingly, different results were found in a retrospective cohort study of individuals with schizophrenia whose access to antipsychotic treatment had been restricted. In this cohort from rural China, those who had access to antipsychotics did substantially better after 14 years than those without access.…”
Section: Efficacy Effectiveness and Tolerabilitymentioning
confidence: 99%
“…Correll et al quote for support a study by Ran et al favoring long‐term use of antipsychotics for schizophrenia in China. However, there are many weaknesses in that study.…”
mentioning
confidence: 99%
“…Historical data suggest that approximately 15% of first episode patients will recover spontaneously and will sustain their recovery but far fewer will do so after several subsequent episodes. The literature suggests that the introduction of antipsychotics improved this outcome (Alem et al, ; Hegarty, Baldessarini, Tohen, & Waternaux, ; Hegarty, Baldessarini, Tohen, Waternaux, & Oepen, ; Jaaskelainen et al, ; Kurihara, Kato, Reverger, Tirta, & Kashima, ; Ran et al, ). All these studies reported that with passing of the years, the condition of untreated patients worsens more, in comparison with treated patients.…”
Section: Discussionmentioning
confidence: 99%